Truck Drivers and Casual Sex : An Inquiry into the Potential Spread of HIV/AIDS in the Baltic Region - Kulis, Marzena; Chawla, Mukesh; Kozierkiewicz, Adam; Subata, Emilis (Washington, DC: World Bank, 2013)
This study, perhaps the first of its kind in this region, is based on a study that explores the practice of casual sex among truck drivers, and commercial sex workers in the border areas of the Baltic region at a point of time, and, uses this evidence to extrapolate the potential impact on the spread of HIV/AIDS in these countries. While the threat of an HIV/AIDS epidemic cannot be taken lightly in any country of the Europe and Central Asia region, four countries - Poland, Latvia, Lithuania, and Estonia - stand out as being particularly vulnerable. First, the prevalence of HIV/AIDS is relatively high, and is rapidly increasing in locations neighboring these countries to the east, like Ukraine, Kaliningrad, Belarus, and Moldova, where public health conditions are also rapidly deteriorating. Second, because of their geographical location, those four countries stand at the crossroads of the main east-west, and north-south transport corridors, and represent the link between countries of the former Soviet Union and western Europe. The open borders, and rapid transit threatens to broaden the sweep of the HIV epidemic, as drug injectors and sex workers come into contact with other population groups. After the Introduction which provides background, Section 2 reviews similar studies carried out elsewhere in the world. Section 3 describes the methodology employed in this study, followed by a brief description of the data in Section 4. Finally, Section 5 contains a discussion of the results, and policy implications.